KARAKTERISASI PADI LOKAL ASAL KECAMATAN BANGKINANG BARAT DAN KECAMATAN TAMBANG KABUPATEN KAMPAR - Annisa Rilnawati; Aslim Rasyad; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aimed to determine the variability an to identify local rice genotipe collected from West Bangkinang and Tambang, Kampar District. The seventeen accessions were grow in Agricultural Experiment Station University of Riau Pekanbaru from September 2017 to March 2018. This research uses descriptive analysis method which includes characterization activities in 17 local rice accessions.Local rice from the West Bangkinang District and Tambang Subdistrict showed uniform and varied performances. The character of the leaf midrib and panicle shaft shows a uniform performance value. The character of leaf tongue shape, leaf color, leaf length, flag leaf angle, root stem diameter, number of children, color of rootstock section, panicle type and color of grain tip showed varying performance values. The results of the analysis of the diversity of morphological characters in 17 local rice accessions ranged from (0 – 4,971). The leaf midrib color character has a uniform diversity and the panicle type character has a very high diversity.Keywords: local rice, diversity, morphology.